Juridical Analysis of Criminal Act Handling Based on Restorative Justice in Resolving Attempted Murder Cases (Research Study at Lingga Resort Police) - Sinaga, Gopal Gospel; Fadlan, Fadlan; Prasetyasari, Christiani; Nofrial, Ramon; Pasaribu, Juhrin (CV. Rayyan Dwi Bharata, 2023)
This thesis is entitled Juridical Analysis of Handling Criminal Acts Based on Restorative Justice in Resolving Cases of Attempted Murder (Research Study at the Lingga Resort Police). The formulation of the problem is how the law is regulated and also how it is implemented, obstacles and efforts to overcome obstacles in handling criminal acts based on restorative justice in solving the attempted murder case. The aim is to find out legal regulations and their implementation, obstacles and efforts to overcome them. This research uses empirical (field) legal research and normative legal (literature) research. Using research methods consisting of 2 forms. Namely normative law or doctrine and empirical or sociological law. The normative is through applicable articles and the empirical is through interviews. The results of research on resolving criminal acts using a restorative justice approach aim to resolve conflicts that occur between perpetrators and victims and avoid negative effects arising from the current criminal system. Some jurisdictions may have special restorative justice programs designed for attempted murder cases. These programs can involve meetings between perpetrators and victims, as well as community participation, with the aim of promoting understanding, resolution, and reconciliation. Implementation of restorative justice in attempted murder cases can be carried out in stages.